2020
DOI: 10.3390/molecules25112517
|View full text |Cite
|
Sign up to set email alerts
|

Development of Resistance to Endoplasmic Reticulum Stress-Inducing Agents in Mouse Leukemic L1210 Cells

Abstract: Four new variants of L1210 cells resistant to endoplasmic reticulum (ER) stressors, tunicamycin (STun), thapsigargin (SThap), bortezomib (SBor), and MG-132 (SMG-132), were developed via an 18-month periodic cultivation in culture medium with a gradual increase in substance concentration. Multidrug resistance was generated for STun (to tunicamycin, bortezomib and MG-132), SThap (to tunicamycin, thapsigargin and MG-132), SBor (to bortezomib and MG-132), and SMG-132 (to bortezomib and MG-132). These cells were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…BOR inhibited S, R, and T cell proliferation with IC 50 values of 6.0752 ± 1.7656, 4.7708 ± 0.8911, and 3.6738 ± 0.5412 (in nM), respectively ( Figure S2 in the supplementary files ). This result is consistent with previously published data [ 25 ]. Because there were weakly significant differences between the IC 50 values of the S cells and the R or T cells, it can be concluded that BOR affects S, R, and T cells with approximately equal efficacy.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…BOR inhibited S, R, and T cell proliferation with IC 50 values of 6.0752 ± 1.7656, 4.7708 ± 0.8911, and 3.6738 ± 0.5412 (in nM), respectively ( Figure S2 in the supplementary files ). This result is consistent with previously published data [ 25 ]. Because there were weakly significant differences between the IC 50 values of the S cells and the R or T cells, it can be concluded that BOR affects S, R, and T cells with approximately equal efficacy.…”
Section: Resultssupporting
confidence: 94%
“…Cutting AMC from the substrate and plotting the BOR effect as a function of time for 90 min revealed a straight line ( Figure S7A in the Supplementary files ), and similarly, a straight line was obtained when plotting the AADG effect measured for 75 min ( Figure S7B in the supplementary files ), both indicating a zero-order reaction that is typical of enzyme catalysis. In previous work, we observed similar behavior when measuring proteasome activity in L1210 cell variants [ 25 ]. This behavior makes it possible to determine the initial reaction rate of the proteasomal cleavage of a substrate, which is constant throughout the measurement, as the slope of the respective line.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations